RESEARCH ETHICS ON AN INTERNATIONAL SCALE WHAT AUTONOMY FOR PARTICIPANTS? - DUGUET, Anne-Marie (MEDECINE LEGALE DROIT MEDICAL, 2025)
The progress of biomedical knowledge is the result of research that has developed in all fields throughout the world. The organization and supervision of research has evolved according to the objectives and justifications of the experiments, raising the question of the legitimacy of the constraints weighing on the experimenters on the one hand, and on the subjects who lend themselves to the research on the other. Historically, research involving human beings has been marked by failures, complications and scandals which led to reflection following the Nuremberg trial (1947) and professionals proposed international references (notably the Helsinki declaration, 1964). In spite of this, research has continued to be carried out in disregard of some of these recommendations, and more recent scandals have appeared, particularly in southern countries. This work presents a reminder of the evolution of biomedical research from experimentation and its abuses to international recommendations respecting the principles of research ethics and the autonomy of participants.